1995
DOI: 10.3354/meps120099
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent variations in phytoplankton and protozoan community structure across the St. Lawrence River transition region

Abstract: We evaluated 2 contrasting perspectives on the St Lawrence Estuary maxlmum turb~dlty zone (MTZ) the f~r s t being that ~t is a zone of stress and mortal~ty for the plankton community, the second that it is a biologically productive area with a complex structured food w e b Two crulses were undertaken under different hydrolog~c reglmes one at the end of the spnng flood penod and the other durlng mean summer flow conditions The same pattern of change in conlmunlty structure of the phytoplankton and protozoa (2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…The d 13 C values of the ETZ consumers are intermediate between those of the freshwater protists, .10-mm seston, and estuarine algae, and consequently these consumers may rely on a combination of these sources. The observations are also consistent with a previous study that found that the maximum turbidity zone of the ETZ acted as a retention zone wherein diatoms and larger particles advected from upstream and produced in situ were concentrated, resulting in a rich feeding zone characterized by high diversity and productivity (Frenette et al 1995). Aggregates and their associated organisms have been documented as an important food source for Eurytemora sp.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The d 13 C values of the ETZ consumers are intermediate between those of the freshwater protists, .10-mm seston, and estuarine algae, and consequently these consumers may rely on a combination of these sources. The observations are also consistent with a previous study that found that the maximum turbidity zone of the ETZ acted as a retention zone wherein diatoms and larger particles advected from upstream and produced in situ were concentrated, resulting in a rich feeding zone characterized by high diversity and productivity (Frenette et al 1995). Aggregates and their associated organisms have been documented as an important food source for Eurytemora sp.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have argued for a dominant role of allochthonous carbon in sustaining food webs in rivers (McCallister et al 2004), whereas other authors have stressed the greater importance of autochthonous sources (Martineau et al 2004 and references therein). The St. Lawrence River ETZ has long been recognized as supporting high biological productivity and an important larval fish nursery, with large standing stocks of phytoplankton and zooplankton (Frenette et al 1995;Winkler et al 2003). In spite of the ecological importance of this ETZ, there has been no analysis of its overall food web structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This argument is justifiable given the high rate of mineralization taking place within the estuary (Tremblay and Gagné 2009) and the inclusion of organic N and P fractions highly valuable as substrate for microbial heterotrophs whose respiration further consumes O 2 . Primary production within the turbid transition zone of the upper estuary is light-limited (Levasseur et al 1984) and supports a rich heterotrophic microbiota (Frenette et al 1995). Calculation of the % contribution of SLR to total estuarine flux using TP (14%) and TN (47%) markedly Assuming that all TP exported to the estuary is mineralized within a year c Assuming that all TN exported to the estuary is mineralized within a year increased the importance or river enrichment to estuarine microbial production, making them all the more significant.…”
Section: Discussionmentioning
confidence: 99%
“…To explain this apparent paradox, Wofsy (1983) suggested the possibility of an exogenous input of algae, among other hypotheses. This is particularly relevant to the St. Lawrence ETM due to the presence of a hydrodynamic entrapment zone that increases the retention time of inorganic and organic particles because they sink into the landward bottom current and are subject to cyclonic recirculation (see Frenette et al 1995 ; Environnement Canada, Service Météorologique), which contribute to the advection of a large phytoplankton biomass (Vincent et al 1996) further downstream (i.e. towards the ETM).…”
Section: Introductionmentioning
confidence: 99%